MICROBES IN YOUR MOUTH: THE HIDDEN PLAYERS IN HEALTH, SICKNESS, AND TOMORROW’S CURES - Gabriela Łocik; Joanna Kośka; Marta Bonarska; Damian Adasik; Katarzyna Herjan; Katarzyna Moliszewska; Julia Mazurek; Julia Załęcka; Kacper Dywan; Martyna Musiorska; Michał Błaszkiewicz; Paweł Kukiełka (International Journal of Innovative Technologies in Social Science, 2025)
Background: The oral microbiome holds a unique position among human microbial communities, featuring over 700 bacterial species along with fungi, viruses, archaea, and protozoa distributed across distinct ecological niches. Development begins prenatally and undergoes significant childhood transitions as tooth eruption creates new colonization sites. Multiple factors shape oral microbial communities, including host genetics, delivery mode, diet, smoking, oral hygiene, alcohol consumption, and antibiotic use. Aim: This study aimed to comprehensively review the oral microbiome’s complexity, development patterns, influencing factors, and associations with oral and systemic diseases. Materials and Methods: A comprehensive literature review examined current evidence on oral microbiome composition, development, influencing factors, and disease associations. Results: Oral microbiome dysbiosis manifests through reduced microbial diversity, depletion of beneficial organisms, and pathogenic species proliferation, contributing to dental caries, periodontal disease, and oropharyngeal cancers. Growing evidence links dysbiosis to systemic conditions including Alzheimer’s disease, diabetes, cardiovascular diseases, and colorectal cancers through bacterial translocation and inflammatory pathways. The oral cavity’s accessibility enables non-invasive sampling and development of microbial biomarkers for early disease detection. Conclusions: This review highlights microbiome-focused interventions’ potential to address disease at microbial roots rather than treating symptoms, creating cascading positive effects throughout the body. As the gateway to human health, the oral microbiome represents a critical frontier in modern medicine deserving increased research attention and investment.